Multilayer structure, method for manufacturing the same, protective sheet for electronic device including the same, and electronic device

By forming a layer of metal oxides and inorganic phosphorus compounds with specific molar ratios and acid dissociation constants, as well as polyvalent metal salts, on a substrate, the problem of insufficient water vapor barrier properties in the prior art is solved, and a high level of water vapor barrier effect is achieved.

CN123036206APending Publication Date: 2026-11-03KURARAY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580024637.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-28
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing multilayer structures cannot achieve the high levels of water vapor barrier properties required by the market in recent years for electronic device applications.

Method used

By forming a layer of reaction products of aluminum-containing metal oxides and inorganic phosphorus compounds and polyvalent metal salts on a substrate, and controlling their molar ratio and acid dissociation constant, a dense layer structure is formed to improve water vapor barrier properties.

Benefits of technology

It achieves excellent water vapor barrier properties to meet market demands, and further improves barrier performance by adjusting the molar ratio and acid dissociation constant.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

Disclosed is a multilayer structure having a layer (Y) comprising a reaction product (D) of a metal oxide (A) containing an aluminum atom and an inorganic phosphorus compound (BI) and a polyvalent metal salt (F) on a substrate (X), in which layer (Y), the ratio (N M / N P ) of the number of moles (N M ) of metal atoms (M) constituting the metal oxide (A) to the number of moles (N P ) of the inorganic phosphorus compound (BI) satisfies 1.0 or more and 2.4 or less, and the ratio (N G / N M ) of the number of moles (N G ) of metal ions (G) constituting the polyvalent metal salt (F) to the number of moles (N M ) satisfies 0.03 or more and 0.25 or less, the solubility of the polyvalent metal salt (F) in water at 25°C is 20 g / 100 mL or more, and the acid dissociation constant (pKa) of the conjugate acid (H') of anion (H) constituting the polyvalent metal salt (F) is 1.83 or more. M P M P G M G M
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This patent application claims priority under the Paris Convention based on Japanese Patent Application No. 2024-055378 (filed on March 29, 2024), the entire contents of which are incorporated herein by reference.

[0002] This invention relates to multilayer structures and their manufacturing methods, protective sheets for electronic devices comprising multilayer structures, and electronic devices. Background Technology

[0003] Multilayer structures in which gas barrier layers, composed of aluminum or alumina, are formed on plastic films are well-known and used as packaging materials to protect items susceptible to oxygen deterioration (such as food). These gas barrier layers are sometimes formed on plastic films using dry processes such as physical vapor deposition or chemical vapor deposition, and sometimes by coating the reaction products of alumina particles and phosphorus compounds onto the plastic. Furthermore, such multilayer structures are also used as protective films for electronic devices requiring both gas and water vapor barrier properties, with the aim of protecting electronic equipment.

[0004] For example, Patent Document 1 describes a composite structure having a transparent gas barrier layer composed of the reaction products of alumina particles and phosphorus compounds. As one method for forming the gas barrier layer, it describes a method of coating a plastic film with a coating liquid containing alumina particles and phosphorus compounds, followed by drying and heat treatment.

[0005] Furthermore, Patent Document 2 describes a method for improving the resistance of the composite structure described in Patent Document 1 to physical stress by coating a coating liquid containing alumina particles, phosphorus compounds and cations onto a plastic film, followed by drying and heat treatment.

[0006] Existing technical documents Patent documents Patent Document 1: International Publication No. 2011 / 122036 Patent Document 2: International Publication No. 2015 / 141225. Summary of the Invention

[0007] The problem that the invention aims to solve In recent years, as protective films primarily used in electronic devices, there has been a demand for barrier materials with exceptionally high water vapor barrier properties. However, while existing composite structures (multilayer structures) offer some degree of water vapor barrier performance, they sometimes fall short of the high levels of water vapor barrier performance required by the market in recent years. The inventors conducted in-depth research with the goal of achieving even better water vapor barrier performance, and thus completed this invention.

[0008] That is, the purpose of this invention is to provide a multilayer structure with excellent water vapor barrier properties and a method for manufacturing the same, a protective sheet for electronic devices including the multilayer structure, and an electronic device.

[0009] Methods for solving problems The present invention includes the following preferred embodiments.

[0010] [1] A multilayer structure comprising a substrate (X) and a layer (Y) stacked on the substrate (X). Layer (Y) contains the reaction product (D) of a metal oxide (A) containing aluminum atoms (hereinafter sometimes simply referred to as "metal oxide (A)") and an inorganic phosphorus compound (BI), as well as a polyvalent metal salt (F). In layer (Y), the number (N) of moles (M) of metal atoms (M) constituting the metal oxide (A) M The number of moles of inorganic phosphorus compounds (BI) and N P The ratio of (N) M / N P The condition satisfies a value of 1.0 or higher and 2.4 or lower, and the molar number (N) of the metal ions (G) constituting the polyvalent metal salt (F) is... G The number of moles (N) of the metal atoms (M) constituting the metal oxide (A) and the number of moles (N) of the metal atoms (M) constituting the metal oxide (A). M The ratio of (N) G / N M () is above 0.03 and below 0.25, The solubility of polyvalent metal salts (F) in water at 25°C is over 20 g / 100 mL. The acid dissociation constant (pKa) of the conjugate acid (H') of the anion (H) constituting the polyvalent metal salt (F) is greater than 1.83.

[0011] [2] According to the multilayer structure described in [1], the metal ion (G) constituting the polyvalent metal salt (F) is a zinc ion.

[0012] [3] According to the multilayer structure described in [1] or [2], wherein the anion (H) constituting the polyvalent metal salt (F) has a carboxylate anion structure.

[0013] [4] The multilayer structure according to any one of [1] to [3], wherein the total area of ​​the interparticle void portion of layer (Y) in the range of 600 nm × 600 nm is 1500 to 2000 nm. 2 Within the range.

[0014] [5] A multilayer structure according to any one of [1] to [4], wherein a substrate (X) and a layer (Y) are stacked through a layer (Z).

[0015] A method for manufacturing a multilayer structure as described in any one of [6] [1] to [5], comprising: coating a coating liquid (S) containing a metal oxide (A), an inorganic phosphorus compound (BI), a multivalent metal salt (F) and a solvent onto a substrate (X), and then removing the solvent to form a precursor layer of layer (Y); and a step (I) thereof. Process (II) is to heat-treat the precursor layer of layer (Y) to form layer (Y).

[0016] [7] A protective sheet for electronic devices, comprising any one of [1] to [6] a multilayer structure.

[0017] [8] The protective sheet according to claim [7] is a protective sheet for protecting the surface of a photoelectric conversion device, an information display device or a lighting device.

[0018] [9] An electronic device having the protective sheet described in [8].

[0019] The effects of the invention According to the present invention, a multilayer structure with excellent water vapor barrier properties and a method for manufacturing the same, a protective sheet for electronic devices using the multilayer structure, and electronic devices can be provided.

[0020] The multilayer structure of the present invention comprises a substrate (X) and a layer (Y) stacked on the substrate (X). The layer (Y) comprises a reaction product (D) of a metal oxide (A) containing aluminum atoms and an inorganic phosphorus compound (BI) and a polyvalent metal salt (F). In the layer (Y), the number (N) of moles (M) of the metal atoms (M) constituting the metal oxide (A) M The number of moles of inorganic phosphorus compounds (BI) and N P The ratio of (N) M / N P The condition satisfies a value of 1.0 or higher and 2.4 or lower, and the molar number (N) of the metal ions (G) constituting the polyvalent metal salt (F) is... G The number of moles (N) of the metal atoms (M) constituting the metal oxide (A) and the number of moles (N) of the metal atoms (M) constituting the metal oxide (A). M The ratio of (N) G / N M The solubility of the polyvalent metal salt (F) in water at 25°C is greater than 20 g / 100 mL, and the acid dissociation constant (pKa) of the conjugate acid (H') of the anion (H) constituting the polyvalent metal salt (F) is greater than 1.83.

[0021] When the ratio (N) M / N PWhen the concentration of N is 1.0 or higher and 2.4 or lower, the water vapor barrier properties, which are improved by including a polyvalent metal salt (F) under the above conditions, become very excellent, especially when the concentration of N is higher than that of N. M / N P When the pKa is above 1.30, the difference in the acid dissociation constant (pKa) of the conjugate acid (H') of the anion (H) constituting the polyvalent metal salt (F) tends to significantly affect the water vapor barrier properties. Furthermore, when the pKa is higher than that of the N-type anion (F), the difference in the pKa of the conjugate acid (H') of the polyvalent metal salt (F) tends to significantly affect the water vapor barrier properties. G / N M When the value is above 0.03 and below 0.25, it tends to exhibit very good water vapor barrier properties.

[0022] Furthermore, by ensuring that the solubility of the polyvalent metal salt (F) in water at 25°C is greater than 20 g / 100 mL, it tends to exhibit very excellent water vapor barrier properties.

[0023] Furthermore, by setting the acid dissociation constant (pKa) of the conjugate acid (H') of the anion (H) constituting the polyvalent metal salt (F) to 1.83 or higher, it tends to exhibit excellent water vapor barrier properties. Although the reason for this is not yet certain, it is speculated that because the acid dissociation constant (pKa) of the conjugate acid (H') of the anion (H) constituting the polyvalent metal salt (F) is the pKa of phosphoric acid, i.e., 1.83 or higher, it is easy for the metal ion (G) constituting the polyvalent metal salt (F) to form salts with inorganic phosphorus compounds (BI). As a result, when the metal oxide (A) reacts with the inorganic phosphorus compound (BI) to form the reaction product (D), the metal ion (G) constituting the polyvalent metal salt (F) also participates in the above reaction. As a result, the crystallinity of the layer (Y) decreases (i.e., an amorphous part is formed), and a denser layer (i.e., the total area of ​​the interparticle void portion is smaller) is formed (Y), thus exhibiting high water vapor barrier properties. Detailed Implementation

[0024] [Substrate (X)] The material of the substrate (X) is not particularly limited, and substrates made of various materials can be used for the substrate (X). Examples of materials for the substrate (X) include resins such as thermoplastic resins and thermosetting resins; fibrous aggregates such as fabrics and paper; wood; glass; metals; and metal oxides. The substrate (X) preferably contains thermoplastic resins and / or fibrous aggregates, and more preferably contains thermoplastic resins. The form of the substrate (X) is not particularly limited, and it can be a layer such as a film or sheet. As the substrate (X), it is preferable to contain at least one selected from thermoplastic resin films, paper layers, and inorganic vapor-deposited layers (X'), more preferably thermoplastic resin films, and even more preferably thermoplastic resin films.

[0025] Examples of thermoplastic resins used as the base material (X) include, for example, polyolefin resins such as polyethylene and polypropylene; polyester resins such as polyethylene terephthalate (PET), polyethylene 2,6-naphthalate, polybutylene terephthalate, or copolymers thereof; polyamide resins such as nylon-6, nylon-66, and nylon-12; hydroxyl-containing polymers such as polyvinyl alcohol and ethylene-vinyl alcohol copolymers; polystyrene; poly(meth)acrylate; polyacrylonitrile; polyvinyl acetate; polycarbonate; polyarylate; regenerated cellulose; polyimide; polyetherimide; polysulfone; polyethersulfone; polyetheretherketone; ionomer resins, etc. The thermoplastic resin used as the base material (X) is preferably selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, nylon-6, and nylon-66, and more preferably polyethylene terephthalate.

[0026] When the aforementioned thermoplastic resin film is used as the substrate (X), the substrate (X) can be a stretched film or an unstretched film. From the perspective of excellent processing adaptability (printing, lamination, etc.) of the resulting multilayer structure, a stretched film is preferred, and a biaxially stretched film is particularly preferred. The biaxially stretched film can be a biaxially stretched film manufactured by any of the following methods: simultaneous biaxial stretching, successive biaxial stretching, and tubular stretching.

[0027] Examples of paper used as the substrate (X) include kraft paper, high-grade paper, imitation paper, cellophane, parchment, synthetic paper, whiteboard paper, Manila cardboard, milk carton paper, paper cup paper, ivory paper, etc. By using paper as the substrate (X), a multi-layered structure for paper containers can be obtained.

[0028] When the substrate (X) is layered, its thickness is preferably 1 to 1,000 μm from the viewpoint of good mechanical strength and processability of the resulting multilayer structure, more preferably 5 to 500 μm, and even more preferably 9 to 200 μm.

[0029] <Inorganic vapor deposition layer (X')> The inorganic vapor-deposited layer (X') is a layer that typically has barrier properties against oxygen and water vapor, and preferably has transparency. The inorganic vapor-deposited layer (X') can be formed by vapor-depositing an inorganic material. Examples of inorganic materials include metals (e.g., aluminum), metal oxides (e.g., silicon oxide, aluminum oxide), metal nitrides (e.g., silicon nitride), metal oxynitrides (e.g., silicon oxynitride), or metal carbonitrides (e.g., silicon carbonitride). From the viewpoint of excellent barrier properties, an inorganic vapor-deposited layer (X') formed of aluminum oxide, silicon oxide, magnesium oxide, or silicon nitride is preferred.

[0030] The method for forming the inorganic vapor-deposited layer (X') is not particularly limited, and examples include physical vapor phase growth methods such as vacuum evaporation (e.g., resistance heating evaporation, electron beam evaporation, molecular beam epitaxy, etc.), sputtering, and ion plating; and chemical vapor phase growth methods such as thermochemical vapor phase growth (e.g., catalyst chemical vapor phase growth), photochemical vapor phase growth, plasma chemical vapor phase growth (e.g., capacitively coupled plasma, inductively coupled plasma, surface wave plasma, electron cyclotron resonance, dual magnetron sputtering, atomic layer stacking, etc.), and organometallic vapor phase growth. The inorganic vapor-deposited layer (X') can be contained within the substrate (X) as described above, or it can be not contained within the substrate (X). Examples of not containing it within the substrate (X) include depositing the inorganic vapor-deposited layer (X') directly onto the layer (Y) after its formation, or depositing the inorganic vapor-deposited layer (X') on the opposite side of the surface on the substrate (X) where the layer (Y) is formed.

[0031] The thickness of the inorganic vapor-deposited layer (X') varies depending on the type of components constituting the inorganic vapor-deposited layer, and is preferably 0.002 to 0.5 μm, more preferably 0.005 to 0.2 μm, and even more preferably 0.01 to 0.1 μm. Within this range, a thickness that provides good barrier properties and mechanical properties for the multilayer structure can be selected. If the thickness of the inorganic vapor-deposited layer (X') is 0.002 μm or more, it tends to have good barrier properties against oxygen and water vapor. Furthermore, if the thickness of the inorganic vapor-deposited layer (X') is 0.5 μm or less, it tends to maintain the barrier properties of the inorganic vapor-deposited layer (X') after bending.

[0032] [Layer (Y)] Layer (Y) is a layer laminated on substrate (X) and contains the reaction product (D) of metal oxide (A) and inorganic phosphorus compound (BI) and a polyvalent metal salt (F). In layer (Y), the molar number (N) of the metal atoms (M) constituting the metal oxide (A) is... M The number of moles (N) of inorganic phosphorus compounds (BI) and inorganic phosphorus compounds (BI) P The ratio of (N) M / N P The molar number (N) of the metal ion (G) constituting the polyvalent metal salt (F) is 1.0 or higher and 2.4 or lower. G The number of moles (N) of the metal atoms (M) constituting the metal oxide (A) and the number of moles (N) of the metal atoms (M) constituting the metal oxide (A). M The ratio of (N) G / N MThe pKa is 0.03 or more and 0.25 or less. Furthermore, the solubility of the polyvalent metal salt (F) in water at 25°C is 20 g / 100 mL or more, and the acid dissociation constant (pKa) of the conjugate acid (H') of the anion (H) constituting the polyvalent metal salt (F) is 1.83 or more. In the multilayer structure of the present invention, since layer (Y) functions as a water vapor barrier layer, the multilayer structure of the present invention, having layer (Y), tends to have good water vapor barrier properties. The arrangement of layer (Y) is not particularly limited as long as it is stacked on top of the substrate layer (X). For example, it can be stacked with the substrate (X) through layer (Z) as described later, or it can be directly stacked on the substrate (X). From the viewpoint of good adhesion between the substrate (X) and layer (Y), layer (Y) is preferably stacked through layer (Z). In particular, a configuration in which the substrate (X) and layer (Z) are directly stacked, and layer (Z) and layer (Y) are also directly stacked, is preferred.

[0033] <Aluminum-containing metal oxides (A)> The metal atom (M) constituting the metal oxide (A) is at least one metal atom selected from metals belonging to Groups 2 to 14 of the periodic table, and includes at least an aluminum atom. The metal atom (M) may be an aluminum atom alone, or it may include an aluminum atom and other metal atoms. It should be noted that two or more metal oxides (A) may be used in combination. Examples of metal atoms other than aluminum include, for example, metals from Group 2 of the periodic table such as magnesium and calcium; metals from Group 12 of the periodic table such as zinc; metals from Group 13 of the periodic table; metals from Group 14 of the periodic table such as silicon; and transition metals such as titanium and zirconium. It should be noted that silicon is sometimes classified as a half-metal, but in this specification, silicon is included within the category of metals. From the viewpoint of processability and excellent gas barrier properties of the resulting multilayer structure, at least one metal atom (M) selected from titanium and zirconium is preferred as the metal atom (M) that can be used in combination with aluminum.

[0034] The proportion of aluminum atoms in the metal atoms (M) is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and can be 95 mol% or more, or can be 100 mol%. Examples of metal oxides (A) include metal oxides manufactured by methods such as liquid-phase synthesis, gas-phase synthesis, and solid-state pulverization.

[0035] The metal oxide (A) can be a hydrolysis condensate of a compound (E) containing a metal atom (M) bonded to a hydrolyzable characteristic group. Examples of such characteristic groups include halogen atoms, NO3, alkoxy groups with 1 to 9 carbon atoms optionally having substituents, aryloxy groups with 6 to 9 carbon atoms optionally having substituents, acyloxy groups with 2 to 9 carbon atoms optionally having substituents, alkenoxy groups with 3 to 9 carbon atoms optionally having substituents, β-diketone groups with 5 to 15 carbon atoms optionally having substituents, or diacylmethyl groups with 1 to 9 carbon atoms optionally having substituents. The hydrolysis condensate of compound (E) can essentially be considered as a metal oxide (A). Therefore, in this specification, the hydrolysis condensate of compound (E) is sometimes referred to as "metal oxide (A)". That is, in this specification, "metal oxide (A)" can be understood as "hydrolysis condensate of compound (E)," and "hydrolysis condensate of compound (E)" can also be understood as "metal oxide (A)".

[0036] <A compound (E) containing a metal atom (M) bonded to a hydrolyzable characteristic group> From the perspective of easy control of the reaction with inorganic phosphorus compound (BI) and the excellent gas barrier properties of the resulting multilayer structure, compound (E) preferably contains aluminum-containing compound (Ea), which will be described later.

[0037] Examples of compounds (Ea) include aluminum chloride, aluminum nitrate, aluminum acetate, tris(2,4-pentanedione)aluminum, trimethoxyaluminum, triethoxyaluminum, tri-n-propoxyaluminum, triisopropoxyaluminum, tri-n-butoxyaluminum, trisec-butoxyaluminum, tritert-butoxyaluminum, and tritert-butoxyaluminum, among which aluminum alkoxyaluminum is preferred, and at least one selected from triisopropoxyaluminum and trisec-butoxyaluminum is more preferred. Two or more compounds (Ea) may be used in combination as compound (E).

[0038] Furthermore, compound (E) may contain compounds (Eb) that include metal atoms (M) other than aluminum. Examples of compounds (Eb) include titanium compounds such as tetra(2,4-pentanedione-based)titanium, tetramethoxytitanium, tetraethoxytitanium, tetraisopropoxytitanium, tetran-butoxytitanium, and tetra(2-ethylhexyloxy)titanium; and zirconium compounds such as tetra(2,4-pentanedione-based)zirconium, tetran-propoxyzirconium, and tetran-butoxyzirconium. These compounds may be used individually or in combination of two or more compounds (Eb).

[0039] The proportion of compound (Ea) in compound (E) is not particularly limited, but is preferably 80 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and can be 100 mol%.

[0040] By hydrolyzing compound (E), at least a portion of the hydrolyzable characteristic groups of compound (E) are converted into hydroxyl groups. Then, condensation occurs through its hydrolysate, forming a compound in which metal atoms (M) are bonded by oxygen atoms (O). Repeating this condensation process forms a compound that can essentially be considered a metal oxide. It should be noted that hydroxyl groups are typically present on the surface of the metal oxide (A) formed in this manner.

[0041] In this specification, the metal oxide (A) can be a compound in which the ratio of [the number of moles of oxygen atoms (O) bonded only to the metal atom (M)] / [the number of moles of metal atoms (M)] is 0.8 or more. Here, the oxygen atoms (O) bonded only to the metal atom (M) are the oxygen atoms (O) in the structure represented by MOM, excluding oxygen atoms bonded to both the metal atom (M) and hydrogen atoms (H) as in the structure represented by MOH. The above-mentioned ratio of the metal oxide (A) is preferably 0.9 or more, more preferably 1.0 or more, and even more preferably 1.1 or more. There is no particular upper limit to this ratio, and if the valence of the metal atom (M) is set to n, it is usually expressed as n / 2.

[0042] For the aforementioned hydrolysis-condensation to occur, it is crucial that the compound (E) possesses characteristic hydrolytic groups. Without these groups, the hydrolysis-condensation reaction either does not occur or is extremely slow, making it difficult to prepare the target metal oxide (A).

[0043] The hydrolysis condensate of compound (E) can be manufactured, for example, by a method employed in a known sol-gel process and from a specific raw material. The raw material can be at least one selected from compound (E), a partially hydrolyzed product of compound (E), a completely hydrolyzed product of compound (E), a compound formed by the partial hydrolysis condensation of compound (E), and a compound formed by the condensation of a portion of the completely hydrolyzed product of compound (E).

[0044] It should be noted that the metal oxide (A) supplied for mixing with the inorganic phosphorus compound (BI) described later is preferably substantially free of phosphorus atoms.

[0045] <Inorganic Phosphorus Compounds (BI)> Inorganic phosphorus compounds (BI) contain sites capable of reacting with metal oxides (A), typically containing multiple such sites, preferably 2 to 20. These sites include those capable of undergoing condensation reactions with functional groups (e.g., hydroxyl groups) present on the surface of the metal oxide (A), such as halogen atoms directly bonded to phosphorus atoms, oxygen atoms directly bonded to phosphorus atoms, etc. The functional groups (e.g., hydroxyl groups) present on the surface of the metal oxide (A) are usually bonded to the metal atoms (M) constituting the metal oxide (A).

[0046] Examples of inorganic phosphorus compounds (BI) include phosphoric acid, diphosphoric acid, triphosphoric acid, polyphosphoric acid condensed with four or more phosphoric acid molecules, phosphorous acid, phosphonic acid, phosphonous acid, hypophosphonic acid, trivalent phosphonic acid, and oxyacids of phosphorus, as well as their salts (e.g., sodium phosphate) and their derivatives (e.g., halides (e.g., phosphoryl chloride), dehydrated products (e.g., phosphorus pentoxide)). One type can be used alone, or two or more can be used in combination. From the viewpoint of improving the stability of the coating solution (S) and the gas barrier properties of the resulting multilayer structure, it is preferable to use phosphoric acid alone or in combination with other inorganic phosphorus compounds (BI). When using phosphoric acid in combination with other inorganic phosphorus compounds (BI), it is preferable that 50 mol% or more of the inorganic phosphorus compound (BI) is phosphoric acid.

[0047] <Reaction Product (D)> The reaction product (D) is obtained by reacting a metal oxide (A) with an inorganic phosphorus compound (BI). The reaction product (D) can be a compound formed by reacting the metal oxide (A) with the inorganic phosphorus compound (BI) and further compounds, for example, a compound formed by reacting the metal oxide (A), the inorganic phosphorus compound (BI), and the metal ion (G) constituting the polyvalent metal salt (F) described later. Even when the metal ion (G) constituting the polyvalent metal salt (F) is part of the reaction product (D), the molar number of the metal ion (G) constituting the reaction product (D) is included in the molar number (N) of the metal ion (G) constituting the polyvalent metal salt (F) described later. G Similarly, the molar number of metal atoms (M) constituting the reaction product (D) and the molar number of phosphorus atoms from the inorganic phosphorus compound (BI) are both included in the molar number (N) of metal atoms (M) constituting the metal oxide (A) described later. M The number of moles of inorganic phosphorus compounds (BI) and N P )middle.

[0048] In the infrared absorption spectrum of layer (Y), 800–1400 cm⁻¹ -1 The maximum absorption wavenumber in the region is preferably between 1080 and 1130 cm⁻¹. -1 The range is as follows. For example, in the reaction of a metal oxide (A) with an inorganic phosphorus compound (BI) to form a reaction product (D), the metal atom (M) from the metal oxide (A) and the phosphorus atom (P) from the inorganic phosphorus compound (BI) form a bond denoted as MOP via an oxygen atom (O). As a result, a characteristic absorption band originating from this bond is generated in the infrared absorption spectrum of the reaction product (D). This band is located in the range of 1080–1130 cm⁻¹. -1When a characteristic absorption band based on MOP bonds is observed in the region, the resulting multilayer structure exhibits excellent gas barrier properties. In particular, this characteristic absorption band is observed in the 800–1400 cm⁻¹ range, where absorption from bonds between various atoms and oxygen atoms is typically observed. -1 When the region exhibits the strongest absorption, the resulting multilayer structure demonstrates superior water vapor barrier properties.

[0049] In contrast, when metal compounds such as metal alkoxides or metal salts are premixed with inorganic phosphorus compounds (BI) and then subjected to hydrolysis-condensation, the metal atoms derived from the metal compound and the phosphorus atoms derived from the inorganic phosphorus compound (BI) mix and react in a substantially uniform manner to obtain a complex. In this case, the infrared absorption spectrum shows a concentration of 800–1400 cm⁻¹. -1 The maximum absorption wavenumber in the region will deviate from 1080–1130 cm⁻¹ -1 The range.

[0050] In the infrared absorption spectrum of layer (Y), from the viewpoint of the gas barrier properties of the resulting multilayer structure, 800–1400 cm⁻¹ -1 The half-width of the maximum absorption band within the region is preferably 200 cm. -1 The following is a preferred value: 150cm -1 Hereinafter, 100cm is further preferred. -1 The following is particularly preferred: 50cm -1 the following.

[0051] The infrared absorption spectrum of layer (Y) can be measured using a Fourier transform infrared spectrophotometer (PerkinElmer SpectrumOne) with a measurement range of 800–1400 cm⁻¹, employing the attenuated total reflectance method. However, in cases where the aforementioned methods are not feasible, measurements can be performed using reflectance measurements such as reflection absorption, external reflection, and attenuated total reflectance; transmission measurements can be performed by scraping layer (Y) from a multilayer structure; the Neugür method; or the tablet method; but these methods are not limited to these.

[0052] Additionally, layer (Y) may locally contain non-reactive metal oxides (A) and / or inorganic phosphorus compounds (BI).

[0053] In layer (Y), the number (N) of moles (M) of metal atoms (M) constituting the metal oxide (A) M The number of moles (N) of inorganic phosphorus compounds (BI) and inorganic phosphorus compounds (BI) P The ratio of (N) M / N P The value must be greater than 1.0 and less than 2.4. When the ratio (N) M / N PWhen the concentration is within the above range, it tends to exhibit excellent water vapor barrier properties. This is especially true when the concentration is higher than that of nitrogen (N). M / N P When the pKa is above 1.30, the difference in the acid dissociation constant (pKa) of the conjugate acid (H') of the anion (H) constituting the polyvalent metal salt (F) tends to significantly affect the water vapor barrier properties. For example, when the pKa is higher than that of N, the difference in the pKa of the conjugate acid (H') of the anion (H) constituting the polyvalent metal salt (F) tends to significantly affect the water vapor barrier properties. M / N P When the pKa is 1.15, the water vapor barrier properties do not differ significantly between the case where layer (Y) contains zinc chloride (different from the polyvalent metal salt (F) with a pKa of -5.90 for the conjugate acid (H') of the anion (H)) and the case where layer (Y) does not contain zinc chloride. However, when compared to (N) M / N P When the ratio is 1.30 or higher, the water vapor barrier properties (water vapor permeability) differ by about one order of magnitude in the same configuration (comparison of Comparative Example 1 and Comparative Example 2 described later). On the other hand, in the case of the layer (Y) containing an appropriate amount of polyvalent metal salt (F) of the present invention, when the ratio (N) is higher... M / N P When the N0 ratio is above 1.0 and below 2.4, it tends to exhibit excellent water vapor barrier properties. Therefore, especially when the N0 ratio is above 1.0 and below 2.4, it exhibits excellent water vapor barrier properties. M / N P When the pKa is above 1.30, the type of polyvalent metal salt (especially the acid dissociation constant (pKa) of the conjugate acid (H') of the anion (H) has a significant effect on water vapor barrier properties, further increasing the difficulty of prediction as conceived in this invention. However, through in-depth research, the inventors have found that, particularly when the pKa is higher than that of the N-ion (H'), the water vapor barrier properties are significantly affected. M / N P When the N value is 1.30 or higher, multilayer structures with layers (Y) containing appropriate amounts of polyvalent metal salts (F) tend to exhibit superior water vapor barrier properties. M / N P The ratio of N to N is preferably 1.15 or higher, more preferably 1.30 or higher. Furthermore, the ratio of N to N is... M / N P The ratio (N) is preferably 2.1 or less, more preferably 1.9 or less, and even more preferably 1.6 or less. M / N P When the molar ratio is within the aforementioned range, there is a tendency to further improve water vapor barrier properties. Excellent gas barrier performance can be obtained within this range. This molar ratio in layer (Y) can be adjusted, for example, by the mixing ratio of metal oxide (A) and inorganic phosphorus compound (BI) in the coating solution (S) used to form layer (Y), as described later. This molar ratio in layer (Y) is generally the same as the ratio in coating solution (S).

[0054] <Polyvalent metal salts (F)> Layer (Y) contains a polyvalent metal salt (F). The polyvalent metal salt (F) may be contained in layer (Y) in its polyvalent metal salt (F) state, may form a salt with an inorganic phosphorus compound (BI), or may constitute part of the reaction product (D) formed by the metal ion (G) of the polyvalent metal salt (F). The polyvalent metal salt (F) is a salt of metal ion (G) and anion (H). The valence of the metal ion (G) is preferably 2 or more and 3 or less, more preferably 2. As for the metal ion (G), there is no particular limitation as long as it is an ion that can form a polyvalent metal, and examples include magnesium ion, calcium ion, titanium ion, zirconium ion, lanthanide ion (e.g., lanthanum ion), vanadium ion, manganese ion, iron ion, cobalt ion, nickel ion, copper ion, zinc ion, aluminum ion, and ammonium ion, etc., wherein, preferably, at least one is selected from magnesium ion, calcium ion, lanthanide ion (e.g., lanthanum ion) and zinc ion, more preferably zinc ion. When the metal ion (G) is zinc ion, the multilayer structure of the present invention tends to have better water vapor barrier properties.

[0055] The acid dissociation constant (pKa) of the conjugate acid (H') of the anion (H) is 1.83 or higher. The pKa is preferably 2.00 or higher, more preferably 3.00 or higher, and even more preferably 4.00 or higher. On the other hand, the pKa is preferably 20.0 or lower, more preferably 17.0 or lower, and can be 10.0 or lower, 7.0 or lower, 6.0 or lower, or 5.0 or lower. When the pKa is within the above range, the multilayer structure of the present invention tends to have excellent water vapor barrier properties. It should be noted that the acid dissociation constant is based on the revised 6th edition of the Basic Chemical Compendium (Maruzen Publishing).

[0056] As an anion (H), it is preferably an ion having a carboxylate anion structure, more preferably a fatty acid ion, even more preferably a lower fatty acid ion with 10 or fewer carbon atoms, and even more preferably a lower saturated fatty acid ion. Specifically, it is preferably an ion that is easily soluble in polar solvents such as water or alcohol, such as formic acid ion, acetate ion, propionate ion, butyrate ion, isobutyrate ion, acrylic acid ion, crotonate ion, itaconic acid ion, malonic acid ion, adipic acid ion, succinate ion, lactate ion, malic acid ion, citrate ion, aconitate ion, tartaric acid ion, benzoic acid ion, and salicylic acid ion. Preferably, it is selected from at least one of formic acid ion, acetate ion, propionate ion, acrylic acid ion, malonic acid ion, and lactate ion, and more preferably acetate ion.

[0057] That is, the polyvalent metal salt (F) may include zinc formate, zinc acetate, zinc propionate, zinc lactate, zinc malate, zinc citrate, zinc carbonate, magnesium acetate, calcium acetate, iron acetate, copper acetate, cobalt acetate, barium acetate, lanthanum acetate and their hydrates, wherein preferably at least one is selected from zinc formate, zinc acetate, zinc lactate, magnesium acetate, calcium acetate, iron acetate and their hydrates, more preferably zinc acetate and its hydrates.

[0058] The polyvalent metal salt (F) has a solubility of 20 g / 100 mL or more in water at 25°C. If the solubility is less than 20 g / 100 mL, the solubility of the polyvalent metal salt (F) may be insufficient when preparing the coating solution (S) described later, resulting in insufficient water vapor barrier properties of the obtained multilayer structure. The solubility is preferably 25 g / 100 mL or more, more preferably 30 g / 100 mL or more, and can be less than 200 g / 100 mL or less. The solubility can be determined by known methods.

[0059] As a method for identifying the types of polyvalent metal salts (F) in layer (Y), in addition to methods of identification by raw materials, methods such as analysis by TOF-SIMS can also be listed. For example, in the case of zinc acetate used in the examples described later, as the zinc acetate content increases, an increase in the fragment peak of acetic acid source confirmed by TOF-SIMS can be observed.

[0060] When the surface of the layer (Y) stacked on the substrate (X) is observed using an ultra-high resolution field emission scanning electron microscope or similar instrument, the state of particle packing can be confirmed. Layer (Y) reduces the interparticle voids by incorporating the reaction product (D) of a metal oxide (A) and an inorganic phosphorus compound (BI) and a polyvalent metal compound (F). By reducing the interparticle voids, water vapor molecules permeating through the voids are suppressed, resulting in a tendency to exhibit high water vapor barrier properties. The total area of ​​the interparticle voids in layer (Y) within the range of 600 nm × 600 nm is preferably 1500–2000 nm. 2 When the total area of ​​the interparticle voids is within the above-mentioned range, it tends to have better water vapor barrier properties. This area can be 1600 nm. 2 The above can also be 1650nm. 2 The above is preferred, with 1920nm being the more desirable. 2 The preferred option is 1840nm. 2 The total area of ​​the interparticle voids can be determined by the type of polyvalent metal salt (F) or polyvalent metal used, the content of the polyvalent metal salt (F) (or the ratio (N)). G / N M )), ratio (N) M / NP Adjustments can be made using [the method described in the examples]. It should be noted that the interparticle voids in this specification can be measured using images captured by an ultra-high resolution field emission scanning electron microscope (UPES). The bright areas (dark areas) below the average brightness value of -2σ in the UPES images are defined as interparticle voids. The total area of ​​the interparticle voids is determined by counting the area of ​​these voids using image processing software. Specifically, the measurement can be performed using the methods described in the examples.

[0061] The thickness of layer (Y) (when the multilayer structure has two or more layers (Y), the total thickness of each layer (Y)) is preferably 0.05 to 4.0 μm, more preferably 0.1 to 2.0 μm. By thinning layer (Y), the dimensional changes of the multilayer structure during processing such as printing and lamination can be minimized. Furthermore, since the flexibility of the multilayer structure is increased, its mechanical properties can also approach those of the substrate itself. When the multilayer structure of the present invention has two or more layers (Y), from the viewpoint of gas barrier properties, the thickness of each layer (Y) is preferably 0.05 μm or more. The thickness of layer (Y) can be controlled by the concentration of the coating liquid (S) used to form layer (Y) (described later) or by its coating method. The thickness of layer (Y) can be determined by observing the cross-section of the multilayer structure using a scanning electron microscope or a transmission electron microscope.

[0062] In addition to the above-mentioned components, layer (Y) may also contain at least one selected from organophosphorus compounds (BO) and polymers (F).

[0063] <Organophosphorus compounds (BO)> The organophosphorus compound (BO) is preferably a polymer (BOa) or an organophosphorus compound (BOb) having multiple phosphorus atoms.

[0064] <Polymers with multiple phosphorus atoms (BOa)> Examples of functional groups containing phosphorus atoms in the polymer (BOa) include phosphate groups, phosphorous groups, phosphonic acid groups, phosphonic acid groups, trivalent phosphonic acid groups, and functional groups derived from them (e.g., salts, (partial) ester compounds, halides (e.g., chlorides), dehydrates), etc., among which phosphate groups and phosphonic acid groups are preferred, and phosphonic acid groups are more preferred.

[0065] Examples of polymers (BOa) include, for instance, phosphoryl (meth)acrylate polymers such as 6-[(2-phosphorylacetyl)oxy]hexyl acrylate, 2-phosphoryloxyethyl methacrylate, phosphoryl methyl methacrylate, 11-phosphoryl undecyl methacrylate, and 1,1-diphosphoryl ethyl methacrylate; vinyl phosphonic acid polymers such as 2-propen-1-phosphonic acid, 4-vinylbenzylphosphonic acid, and 4-vinylphenylphosphonic acid; vinyl hypophosphonic acid polymers such as 4-vinylbenzyl hypophosphonic acid; and phosphorylated starch. The polymer (BOa) can be a homopolymer of a monomer having at least one functional group containing a phosphorus atom, or a copolymer of two or more monomers. Furthermore, as a polymer (BOa), two or more polymers formed from a single monomer can be used in combination. Preferably, polymers of phosphoryl (meth)acrylates and polymers of vinyl phosphonic acids are used, more preferably polymers of vinyl phosphonic acids. That is, as a polymer (BOa), poly(vinyl phosphonic acid) is preferred. Alternatively, the polymer (BOa) can also be obtained by hydrolysis after homopolymerization or copolymerization of vinylphosphonic acid derivatives such as vinylphosphonic acid halides or vinylphosphonic esters.

[0066] Furthermore, the polymer (BOa) can be a copolymer of a monomer having at least one functional group containing a phosphorus atom and other vinyl monomers. Examples of other vinyl monomers capable of copolymerizing with monomers having functional groups containing phosphorus atoms include (meth)acrylic acid, (meth)acrylates, acrylonitrile, methacrylonitrile, styrene, nucleosubstituted styrene, alkyl vinyl ethers, alkyl vinyl esters, perfluoroalkyl vinyl ethers, perfluoroalkyl vinyl esters, maleic acid, maleic anhydride, fumaric acid, itaconic acid, maleimide, phenylmaleimide, etc., among which (meth)acrylates, acrylonitrile, styrene, maleimide, and phenylmaleimide are preferred.

[0067] In order to obtain a multilayer structure with better bending resistance, the proportion of structural units derived from monomers having functional groups containing phosphorus atoms in all structural units of the polymer (BOa) is preferably 10 mol% or more, more preferably 20 mol% or more, further preferably 40 mol% or more, particularly preferably 70 mol% or more, and can be 100 mol%.

[0068] The molecular weight of the polymer (BOa) is not particularly limited, but the number average molecular weight is preferably in the range of 1,000 to 100,000. If the number average molecular weight is in this range, it is possible to achieve a high level of improvement in flexural strength brought about by the laminate (Y) and viscosity stability of the coating liquid (S) when using the coating liquid (S) described later.

[0069] In the case where layer (Y) of a multilayer structure contains an inorganic phosphorus compound (BI) and a polymer (BOa), the mass W of the inorganic phosphorus compound (BI) in layer (Y) is... BI With the mass W of the polymer (BOa) BOa The ratio of W BOa / W BI Ideally, W should satisfy 0.01 / 99.99 ≤ W. BOa / W BI From the perspective of superior barrier performance, given the relationship of <6.00 / 94.00, it is more preferable to satisfy 0.10 / 99.90≤W. BOa / W BI The relationship < 4.50 / 95.50 is further optimized to satisfy 0.20 / 99.80 ≤ W. BOa / W BI The relationship < 4.00 / 96.00 is particularly preferred, satisfying 0.50 / 99.50 ≤ W. BOa / W BI The relationship is <3.50 / 96.50. That is, with W. BOa Compared to trace amounts greater than 0.01 and less than 6.00, W is preferred. BI Large quantities are used where the concentration is greater than 94.00 and less than 99.99. It should be noted that even if the inorganic phosphorus compound (BI) and / or organophosphorus compound (BOa) in layer (Y) react, the portion of the inorganic phosphorus compound (BI) and / or organophosphorus compound (BOa) constituting the reaction product (D) is considered as inorganic phosphorus compound (BI) and / or organophosphorus compound (BOa). In this case, the mass of the inorganic phosphorus compound (BI) and / or organophosphorus compound (BOa) used to form the reaction product (D) (the mass of the inorganic phosphorus compound (BI) and / or organophosphorus compound (BOa) before the reaction) is included in the mass of the inorganic phosphorus compound (BI) and / or organophosphorus compound (BOa) in layer (Y).

[0070] <Organophosphorus compounds (BOb)> In organophosphorus compounds (BOb), phosphorus atoms with at least one hydroxyl group are bonded to polar groups via alkylene chains or polyoxyalkylene chains with 3 to 20 carbon atoms. Compared to metal oxides (A), inorganic phosphorus compounds (BI), and their reaction products (D), organophosphorus compounds (BOb) have lower surface free energy and segregate towards the surface during the precursor formation of layer (Y). Because organophosphorus compounds (BOb) possess phosphorus atoms with at least one hydroxyl group that can react with the components contained in layer (Y), and polar groups that can react with other components (e.g., adhesive layer (I), other layers (J) (e.g., ink layer)), adhesion is improved, and interlayer adhesion can be maintained even after cooking under stress. From this perspective, appearance defects such as interlayer peeling can be suppressed.

[0071] Examples of organophosphorus compounds (BOb) include 3-hydroxypropylphosphonic acid, 4-hydroxybutylphosphonic acid, 5-hydroxypentylphosphonic acid, 6-hydroxyhexylphosphonic acid, 7-hydroxyheptylphosphonic acid, 8-hydroxyoctylphosphonic acid, 9-hydroxynonylphosphonic acid, 10-hydroxydecylphosphonic acid, 11-hydroxyundecylphosphonic acid, 12-hydroxydodecylphosphonic acid, 13-hydroxytridecylphosphonic acid, 14-hydroxytetradecylphosphonic acid, 15-hydroxypentadecanylphosphonic acid, and 16-hydroxyhexadecane. Phosphonic acid, 17-hydroxyheptadecylphosphonic acid, 18-hydroxyoctadecylphosphonic acid, 19-hydroxynonadecanylphosphonic acid, 20-hydroxyeicosylphosphonic acid, 3-hydroxypropyl dihydrogen phosphate, 4-hydroxybutyl dihydrogen phosphate, 5-hydroxypentyl dihydrogen phosphate, 6-hydroxyhexyl dihydrogen phosphate, 7-hydroxyheptyl dihydrogen phosphate, 8-hydroxyoctyl dihydrogen phosphate, 9-hydroxynonyl dihydrogen phosphate, 10-hydroxydecyl dihydrogen phosphate, 11-hydroxyundecyl dihydrogen phosphate, 12-hydroxypropyl dihydrogen phosphate -Hydroxydodecyl phosphate, 13-hydroxytridecyl phosphate, 14-hydroxytetradecyl phosphate, 15-hydroxypentadecanyl phosphate, 16-hydroxyhexadecyl phosphate, 17-hydroxyheptadecyl phosphate, 18-hydroxyoctadecyl phosphate, 19-hydroxynonadecanyl phosphate, 20-hydroxyeicosyl phosphate, 3-carboxypropylphosphonic acid, 4-carboxybutylphosphonic acid, 5-carboxypentylphosphonic acid, 6-carboxyhexylphosphonic acid Phosphonic acids, including 7-carboxyheptaylphosphonic acid, 8-carboxyoctylphosphonic acid, 9-carboxynonylphosphonic acid, 10-carboxydecylphosphonic acid, 11-carboxyundecylphosphonic acid, 12-carboxydodecylphosphonic acid, 13-carboxytridedecylphosphonic acid, 14-carboxytetradecylphosphonic acid, 15-carboxypentadecanylphosphonic acid, 16-carboxyhexadecylphosphonic acid, 17-carboxyheptadecylphosphonic acid, 18-carboxyoctadecylphosphonic acid, 19-carboxynonadecanylphosphonic acid, and 20-carboxyeicosylphosphonic acid, can be used alone or in combination of two or more.

[0072] In the case where layer (Y) of a multilayer structure contains both inorganic phosphorus compound (BI) and organophosphorus compound (BOb), the molar number M of the organophosphorus compound (BOb) in layer (Y) is... BOb Molar number M with inorganic phosphorus compound (BI) BI The ratio of M BOb / M BI Preferably, it satisfies 1.0 × 10 -4 ≤M BOb / M BI ≤2.0×10 -2 From the perspective of improving fit, a relationship that satisfies 3.5 × 10 is preferable. -4 ≤M BOb / M BI ≤1.0×10 -2 From the perspective of improving both sealing and barrier properties, further optimization is performed to meet the 5.0×10 -4 ≤M BOb / M BI ≤6.0×10 -3 The relationship. It should be noted that M... BOb / M BI The number of moles of inorganic phosphorus compound (BI) in M BI It refers to the inorganic phosphorus compound (BI) used to form the reaction product (D).

[0073] When layer (Y) contains an organophosphorus compound (BOb), the C / Al ratio of layer (Y) of the multilayer structure, measured by X-ray photoelectron spectroscopy (XPS), at a distance of 5 nm from the surface of the side not in contact with the substrate (X), is preferably in the range of 0.1 to 15.0, more preferably in the range of 0.3 to 10.0, and even more preferably in the range of 0.5 to 5.0. When the organophosphorus compound (BOb) is present on the surface of layer (Y), it exhibits good adhesion.

[0074] <Polymer (K)> Layer (Y) may comprise a polymer (K) having at least one functional group selected from carbonyl, hydroxyl, carboxyl, carboxylic anhydride, and carboxyl salts. Polymer (K) is preferably a polymer having at least one functional group selected from hydroxyl and carboxyl.

[0075] Examples of polymers (K) include polyethylene glycol; PVA, modified PVA containing 1 to 50 mol% of α-olefin units with 4 or fewer carbon atoms, polyvinyl acetal (polyvinyl butyral, etc.), and other PVA-based polymers; polysaccharides such as cellulose and starch; (meth)acrylic acid polymers such as polyhydroxyethyl (meth)acrylate, poly(meth)acrylic acid, and ethylene-acrylic acid copolymers; and maleic acid polymers such as hydrolysates of ethylene-maleic anhydride copolymers, hydrolysates of styrene-maleic anhydride copolymers, and hydrolysates of isobutylene-maleic anhydride alternating copolymers. Polyethylene glycol and PVA-based polymers are preferred.

[0076] Polymer (K) can be a homopolymer of monomers having polymerizable groups, a copolymer of two or more monomers, or a copolymer of monomers having hydroxyl and / or carboxyl groups with monomers not having such groups. It should be noted that polymers (K) can be used in combination of two or more polymers (K).

[0077] The molecular weight of polymer (K) is not particularly limited, but in order to obtain a multilayer structure with better gas barrier properties and mechanical strength, the weight-average molecular weight of polymer (K) is preferably 5,000 or more, more preferably 8,000 or more, and even more preferably 10,000 or more. The upper limit of the weight-average molecular weight of polymer (K) is not particularly limited, for example, it is 1,500,000 or less.

[0078] From the viewpoint of maintaining a good appearance of the multilayer structure, the content of polymer (K) in layer (Y) is preferably less than 50% by mass, more preferably less than 20% by mass, even more preferably less than 10% by mass, and may also be 0% by mass, based on the mass of layer (Y). Polymer (K) may or may not react with the components in layer (Y).

[0079] Layer (Y) may further contain other components. Examples of other components that may be contained in layer (Y) include crosslinking agents, polymers other than polymer (BOa) and polymer (K), plasticizers, antioxidants, UV absorbers, flame retardants, etc. The content of these other components in layer (Y) of the multilayer structure is preferably 50% by mass or less, more preferably 20% by mass or less, further preferably 10% by mass or less, particularly preferably 5% by mass or less, and may also be 0% by mass (excluding other components).

[0080] [Layer (W)] The multilayer structure of the present invention may have a layer (W) comprising at least one selected from the organophosphorus compound (BO) and the polymer (K) on the layer (Y). When the multilayer structure of the present invention comprises a layer (W), the layer (W) is preferably directly stacked with the layer (Y). The preferred manner in which the organophosphorus compound (BO) and polymer (K) may be contained in the layer (W) is as described above. The multilayer structure of the present invention, comprising a layer (W), tends to have improved bending resistance or improved adhesion with other layers (J) described later.

[0081] Layer (W) may also contain other components, such as crosslinking agents, polymers other than polymer (BOa) and polymer (K), plasticizers, antioxidants, ultraviolet absorbers, flame retardants, etc. The content of the aforementioned other components in layer (W) is preferably 50% by mass or less, more preferably 20% by mass or less, further preferably 10% by mass or less, particularly preferably 5% by mass or less, and may be 0% by mass (excluding other components).

[0082] In the case where the multilayer structure of the present invention includes a layer (W), from the viewpoint that the bending resistance of the multilayer structure of the present invention is improved, the thickness of the layer (W) is preferably 0.005 μm or more. There is no particular upper limit to the thickness of the layer (W), but the improvement effect on bending resistance reaches saturation when it is 1.0 μm or more. Therefore, setting the upper limit of the thickness of the layer (W) to 1.0 μm is preferred from an economic point of view.

[0083] The multilayer structure of the present invention preferably includes a layer (Z) between the substrate (X) and the layer (Y). That is, it is preferable to have a configuration in which the substrate (X) and the layer (Y) are stacked together by the layer (Z). By including the layer (Z), the adhesion between the substrate (X) and the layer (Y) can be improved.

[0084] [Layer (Z)] As an adhesive constituting layer (Z), there are no particular limitations as long as it has adhesive properties between the substrate (X) and the layer (Y), and examples include polyurethane-based adhesives and polyester-based adhesives. By adding small amounts of known additives such as silane coupling agents to these adhesives, the adhesive properties can sometimes be further improved. Examples of silane coupling agents include those with reactive groups such as isocyanate groups, epoxy groups, amino groups, urea groups, and mercapto groups.

[0085] As a polyurethane-based adhesive, known adhesives can be used, but two-component polyurethane-based adhesives that mix and react a polyisocyanate component with a polyol component are preferred. Commercially available two-component polyurethane-based adhesives can be used, such as TAKELAC (registered trademark) and TAKENATE (registered trademark) manufactured by Mitsui Chemicals Co., Ltd.

[0086] As a polyester adhesive, known adhesives can be used. Commercially available products include, for example, ELITEL (registered trademark) KT-0507, KT-8701, KT-8803, KT-9204, KA-5034, KA-3556, KA-1449, KA-5071S, KZA-1449S (all manufactured by Uniqlo); BYRONAL (registered trademark) MD-1200, BYRONAL MD-1480 (all manufactured by Toyobo); PESRESINA-124GP, PESRESINA-684G, PESRESINA-680 (manufactured by Takamatsu Oils & Fats Co., Ltd.), etc.

[0087] Adding vinyl alcohol-based resins, especially polyvinyl alcohol, to polyester adhesives can sometimes further improve adhesion. When using both vinyl alcohol-based and polyester resins, from the viewpoint of maintaining good adhesion and exhibiting higher peel strength, the mass ratio (vinyl alcohol-based resin / polyester resin) is preferably 1 / 99 or more and 50 / 50 or less. From the viewpoint of affinity with vinyl alcohol-based resins, polyester resins with carboxyl groups are preferred. Furthermore, when used as an adhesive, the polyester resin is preferably an aqueous dispersion. By making the polyester resin an aqueous dispersion, it tends to exhibit better affinity with polyvinyl alcohol-based resins. The thickness of layer (Z) is preferably 0.001 to 10.0 μm, more preferably 0.01 to 5.0 μm.

[0088] [Other layers (J)] In the multilayer structure of the present invention, other layers (J) may be included to improve various properties (e.g., heat-sealing properties, barrier properties, mechanical properties). This multilayer structure of the present invention can be manufactured, for example, by laminating a layer (Y) (as needed via a layer (Z)) onto a substrate (X), and then bonding or forming the other layers (J) directly or via an adhesive layer (I') described later. Examples of other layers (J) include, but are not limited to, thermoplastic resin layers such as ink layers, polyolefin layers, and ethylene-vinyl alcohol copolymer resin layers.

[0089] In the case where the multilayer structure of the present invention includes an ink layer, examples of ink layers include films obtained by drying a liquid containing a polyurethane resin containing a pigment (e.g., titanium dioxide) dispersed in a solvent, or films obtained by drying inks or resists for forming electronic circuit wiring with a pigment-free polyurethane resin or other resin as the main agent. As for the coating method of the ink layer, in addition to gravure printing, various coating methods such as wire rod coating, spin coating, and die coating are possible. The thickness of the ink layer is preferably 0.5 to 10.0 μm, more preferably 1.0 to 4.0 μm.

[0090] By making the outermost layer of the multilayer structure of the present invention a polyolefin layer, heat-sealing properties or mechanical properties of the multilayer structure can be imparted. From the viewpoint of improving heat-sealing properties and mechanical properties, the polyolefin is preferably polypropylene or polyethylene. Furthermore, to improve the mechanical properties of the multilayer structure, it is preferable to laminate at least one film selected from films containing polyester, films containing polyamide, and films containing hydroxyl-containing polymers. From the viewpoint of improving mechanical properties, polyethylene terephthalate is preferred as the polyester, nylon-6 is preferred as the polyamide, and ethylene-vinyl alcohol copolymer is preferred as the hydroxyl-containing polymer.

[0091] Other layers (J) may be layers formed by extrusion coating lamination. The extrusion coating lamination method used in this invention is not particularly limited, and known methods may be used. In a typical extrusion coating lamination method, a laminate is produced by feeding molten thermoplastic resin into a T-die and cooling the thermoplastic resin extracted from the flat slit of the T-die.

[0092] Other extrusion coating lamination methods besides the aforementioned single-layer lamination methods include sandwich lamination and tandem lamination. Sandwich lamination involves extruding molten thermoplastic resin onto one substrate and supplying a second substrate from another unwinding machine (winding machine) for bonding to create a laminate. Tandem lamination connects two single-layer laminators to produce a five-layer laminate in a single operation.

[0093] [Adhesive layer (I)] In the multilayer structure of the present invention, an adhesive layer (I) can sometimes be used to improve adhesion to other components (e.g., other layers (J)). The adhesive layer (I) can be composed of an adhesive resin. As an adhesive resin for improving adhesion to the aforementioned other components, a two-component reactive polyurethane adhesive, in which a polyisocyanate component and a polyol component are mixed and reacted, is preferred. In addition, by adding a small amount of additives such as known silane coupling agents to the anchoring agent or adhesive, adhesion can sometimes be further improved. Examples of silane coupling agents include, but are not limited to, silane coupling agents having reactive groups such as isocyanate groups, epoxy groups, amino groups, urea groups, and mercapto groups. By bonding with other components, when the multilayer structure of the present invention is processed by printing or lamination, the deterioration of gas barrier properties or appearance can sometimes be more effectively suppressed, thereby improving the drop strength of packaging materials using the multilayer structure of the present invention.

[0094] The water vapor transmission rate of the multilayer structure of the present invention, measured according to ISO 15106-3:2003 (isobaric method) at 40°C and 0%RH / 90%RH, is preferably 7.0 × 10⁻⁶. -3 g / (m 2(day) or less. Such water vapor permeability means that it exhibits very excellent water vapor barrier properties. More preferably, the water vapor permeability is 6.0 × 10⁻⁶. -3 g / (m 2 ·day) or less, further preferably 5.0×10 -3 g / (m 2 ·day) or less, especially preferred is 4.0×10 -3 g / (m 2 •day) or less. Furthermore, in cases where layers (Y) are present on both sides of the substrate (X), a 7.0 × 10⁻⁶ layer is sometimes preferred. -4 g / (m 2 •day) or less. The water vapor permeability can also be 1.0×10 -4 g / (m 2 ·day) or above.

[0095] [Composition of multi-layered structures] In the multilayer structure of the present invention, at least one set of substrates (X) and layers (Y) are stacked adjacently. The substrates (X) and layers (Y) can be stacked directly or through layers (Z).

[0096] The following are examples of the configuration of the multilayer structure of the present invention, but the multilayer structure of the present invention is not limited to these. Each specific example may also be a combination of multiple configurations. Here, " / " refers to stacking by layers (Z) or directly.

[0097] (1) Layer (Y) / Substrate (X) (2) Layer (Y) / Substrate (X) / Layer (Y) (3) Substrate (X) / Layer (Y) / Layer (Y) / Substrate (X) (4) Layer (Y) / Substrate (X) / Substrate (X) / Layer (Y) (5) Layer (Y) / Substrate (X) / Layer (Y) / Substrate (X) (6) Layer (Y) / Substrate (X) / Layer (Y) / Substrate (X) / Layer (Y) In the above example, the substrate (X) preferably includes a PET layer. In addition, it may further include other layers (J), which may be laminated on the layer (Y) or substrate (X) through an adhesive layer (I).

[0098] [Manufacturing method of multi-layered structures] The matters described with respect to the multilayer structure of the present invention can also be applied to the manufacturing method of the present invention, therefore repeated descriptions are sometimes omitted. Furthermore, the matters described with respect to the manufacturing method of the present invention can also be applied to the multilayer structure of the present invention.

[0099] As a method for manufacturing the multilayer structure of the present invention, examples include manufacturing methods comprising the following steps: applying a coating liquid (S) comprising a metal oxide (A), an inorganic phosphorus compound (BI), a polyvalent metal salt (F) and a solvent onto a substrate (X), and then removing the solvent to form a precursor layer of layer (Y); and a step (II) of heat-treating the precursor layer of layer (Y) to form layer (Y). In manufacturing a multilayer structure containing an organophosphorus compound (BO) or a polymer (K), the coating liquid (S) used in step (I) can contain an organophosphorus compound (BO) or a polymer (K) to form a layer (Y) containing an organophosphorus compound (BO) or a polymer (K). Alternatively, a coating liquid (T) containing an organophosphorus compound (BO) or a polymer (K) can be prepared, and the organophosphorus compound (BO) or polymer (K) can be impregnated into the layer (Y) by applying the coating liquid (T) to the surface of the precursor layer of the layer (Y) obtained in step (I) or the surface of the layer (Y) obtained in step (II) in step (III). Alternatively, a layer (W) can be set on the layer (Y). It should be noted that when a layer (Z) is set between the substrate (X) and the layer (Y), a step of setting an adhesive layer (Z) on the substrate (X) before step (I) can be included.

[0100] <Process (I)> In process (I), a coating liquid (S) containing metal oxide (A), inorganic phosphorus compound (BI), polyvalent metal salt (F) and solvent is applied to the substrate (X), and then the solvent is removed to form a precursor layer (Y).

[0101] Specific methods for preparing the coating solution (S) include: mixing a dispersion of a metal oxide (A) with a solution containing an inorganic phosphorus compound (BI), and then mixing a solution containing a polyvalent metal salt (F); adding an inorganic phosphorus compound (BI) to a dispersion of a metal oxide (A) and then mixing a solution containing a polyvalent metal salt (F); pre-mixing a polyvalent metal salt (F) or a solution containing a polyvalent metal salt (F) in a dispersion of a metal oxide (A) or a solution containing an inorganic phosphorus compound (BI), and then mixing the dispersion of the metal oxide (A) with the solution containing the inorganic phosphorus compound (BI), etc. The mixing temperature is preferably 40°C or lower, more preferably 20°C or lower, and even more preferably 10°C or lower. The coating solution (S) may contain other compounds (e.g., organophosphorus compounds (BO), polymers (K)), and may also contain at least one acid compound (Q) selected from acetic acid, hydrochloric acid, nitric acid, trifluoroacetic acid, and trichloroacetic acid, as needed.

[0102] A dispersion of metal oxide (A) can be prepared, for example, by mixing compound (E), water, and an acid catalyst and organic solvent as needed, according to a known sol-gel method, to induce condensation or hydrolytic condensation of compound (E). When a dispersion of metal oxide (A) is obtained by inducing condensation or hydrolytic condensation of compound (E), the resulting dispersion can be subjected to specific treatments as needed (such as degelation in the presence of the aforementioned acid compound (Q)). The solvent used in preparing the dispersion of metal oxide (A) is not particularly limited, but alcohols such as methanol, ethanol, and isopropanol are preferred; water; or mixtures thereof.

[0103] As a solvent used in solutions containing inorganic phosphorus compounds (BI), it can be appropriately selected according to the type of inorganic phosphorus compound (BI), and water is preferred. As long as it does not hinder the dissolution of inorganic phosphorus compounds (BI), the solvent can contain organic solvents (such as alcohols such as methanol).

[0104] As a solvent used in solutions containing polyvalent metal salts (F), it can be appropriately selected according to the type of polyvalent metal salt (F), and water is preferred. As long as it does not hinder the dissolution of polyvalent metal salts (F), the solvent can contain organic solvents (such as alcohols such as methanol).

[0105] From the viewpoint of the preservation stability of the coating solution and its coatability to the substrate, the solid content concentration of the coating solution (S) is preferably 1 to 20% by mass, more preferably 2 to 15% by mass, and even more preferably 3 to 10% by mass. The aforementioned solid content concentration can be calculated, for example, by dividing the mass of the solid content remaining after distilling off the solvent of the coating solution (S) by the mass of the coating solution (S) supplied for processing.

[0106] The viscosity of the coating liquid (S), measured using a Brookfield rotational viscometer (SB type viscometer: rotor No. 3, rotation speed: 60 rpm), is preferably 6000 mPa·s or less at the coating temperature, more preferably 4000 mPa·s or less, and even more preferably 3000 mPa·s or less. By setting this viscosity to 4000 mPa·s or less, the leveling properties of the coating liquid (S) are improved, resulting in a multilayer structure with a superior appearance. Furthermore, the viscosity of the coating liquid (S) is preferably 50 mPa·s or more, more preferably 100 mPa·s or more, and even more preferably 200 mPa·s or more.

[0107] In the coating solution (S), the preferred molar ratio of metal atoms (M) to phosphorus atoms is the aforementioned ratio (N). M / N P The range of ( ). The molar ratio of metal atoms to phosphorus atoms can be calculated by performing fluorescence X-ray analysis on the dried solid of the coating solution (S).

[0108] There are no particular limitations on the coating of the coating liquid (S), and known methods can be used. Examples of coating methods include casting, dipping, roller coating, gravure coating, screen printing, reverse coating, spraying, kissing coating, die coating, metering rod coating, sealing blade coating, curtain coating, and bar coating.

[0109] There are no particular limitations on the method for removing the solvent (drying process) after coating with the coating liquid (S), and well-known drying methods can be used. Examples of drying methods include hot air drying, hot roller contact drying, infrared heating, and microwave heating.

[0110] The drying temperature is preferably lower than the flow initiation temperature of the substrate (X). The drying temperature after coating with the coating liquid (S) can be, for example, around 60°C to 180°C, more preferably 60°C or higher and less than 140°C, further preferably 70°C or higher and less than 130°C, and particularly preferably 80°C or higher and less than 120°C. The drying time is not particularly limited, but is preferably 1 second or more and less than 1 hour, more preferably 5 seconds or more and less than 15 minutes, and further preferably 5 seconds or more and less than 300 seconds. In particular, when the drying temperature is 100°C or higher (e.g., 100 to 140°C), the drying time is preferably 1 second or more and less than 4 minutes, more preferably 5 seconds or more and less than 4 minutes, and further preferably 5 seconds or more and less than 3 minutes. When the drying temperature is lower than 100°C (e.g., 60 to 99°C), the drying time is preferably 3 minutes or more and less than 1 hour, more preferably 6 minutes or more and less than 30 minutes, and further preferably 8 minutes or more and less than 25 minutes. If the drying conditions of the coating solution (S) are within the above range, there is a tendency to obtain a multilayer structure with better water vapor barrier properties. The solvent is removed by the above drying process, thereby forming a precursor layer (Y).

[0111] In the case of a double-layer (Y) lamination on both sides of a substrate (X), a first layer (precursor layer of the first layer (Y)) is formed by applying a coating liquid (S) to one side of the substrate (X) and then removing the solvent. Next, a second layer (precursor layer of the second layer (Y)) is formed by applying the coating liquid (S) to the other side of the substrate (X) and then removing the solvent. The composition of the coating liquid (S) applied to each side can be the same or different.

[0112] [Process (II)] In step (II), the precursor layer of layer (Y) formed in step (I) is heat-treated to form layer (Y). In step (II), a reaction to generate reaction product (D) is carried out. To ensure the reaction is complete, the heat treatment temperature is preferably 140°C or higher, more preferably 170°C or higher, even more preferably 180°C or higher, and particularly preferably 190°C or higher. If the heat treatment temperature is low, the time required to obtain a sufficient reaction rate will be longer, resulting in a decrease in productivity. The heat treatment temperature varies depending on the type of substrate (X), for example, when a thermoplastic resin film formed from a polyamide resin is used as the substrate (X), the heat treatment temperature is preferably 270°C or lower. In addition, when a thermoplastic resin film formed from a polyester resin is used as the substrate (X), the heat treatment temperature is preferably 240°C or lower. The heat treatment can be carried out in an air atmosphere, a nitrogen atmosphere, an argon atmosphere, etc. The heat treatment time is preferably 1 second to 1 hour, more preferably 1 second to 15 minutes, and even more preferably 5 to 300 seconds.

[0113] Process (II) preferably includes a first heat treatment process (II-1) and a second heat treatment process (II-2). When heat treatment is performed in two or more stages, the temperature of the second heat treatment (hereinafter referred to as the second heat treatment) is preferably higher than the temperature of the first heat treatment (hereinafter referred to as the first heat treatment), more preferably 15°C or more higher than the temperature of the first heat treatment, even more preferably 20°C or more higher, and particularly preferably 30°C or more higher.

[0114] Furthermore, from the viewpoint of obtaining a multilayer structure with good properties, the heat treatment temperature of step (II) (which is the first heat treatment temperature in the case of heat treatment in two or more stages) is preferably higher than the drying temperature of step (I), preferably 30°C or more higher, more preferably 50°C or more higher, even more preferably 55°C or more higher, and particularly preferably 60°C or more higher.

[0115] When heat treatment of process (II) is performed in two or more stages, the temperature of the first heat treatment is preferably 140°C or higher and less than 200°C, and the temperature of the second heat treatment is more preferably 180°C or higher and less than 270°C. The temperature of the second heat treatment is preferably higher than the temperature of the first heat treatment, more preferably 15°C or higher, and even more preferably 25°C or higher. Especially when the heat treatment temperature is 200°C or higher, the heat treatment time is preferably 0.1 seconds to 10 minutes, more preferably 0.5 seconds to 15 minutes, and even more preferably 1 second to 3 minutes. When the heat treatment temperature is below 200°C, the heat treatment time is preferably 1 second to 15 minutes, more preferably 5 seconds to 10 minutes, and even more preferably 10 seconds to 5 minutes.

[0116] [Process (III)] In the aforementioned manufacturing method, when using organophosphorus compounds (BO), polymers (K), and / or other components, the following step (III) may be included: applying a coating liquid (T), obtained by mixing organophosphorus compounds (BO), polymers (K), and / or other components, and a solvent, onto the layer (Y) precursor layer obtained in step (I), the layer (Y) obtained in step (II), or the layer (Y) precursor layer after step (II-1), and subjecting it to drying. If step (III) is performed after step (II-1), it is preferable to perform step (II-2) after the drying process of step (III). In step (III), the amount of coating liquid (T) may be increased to form a layer (W) on the layer (Y).

[0117] The solvent used in the coating liquid (T) can be appropriately selected according to the type of organophosphorus compound (BO), polymer (K) and / or other components, preferably alcohols such as methanol, ethanol, and isopropanol; water; or a mixture thereof.

[0118] From the viewpoint of the solution's storage stability and coatability, the concentration of solid components in the coating solution (T) is preferably 0.01 to 60% by mass, more preferably 0.1 to 50% by mass, and even more preferably 0.2 to 40% by mass. The concentration of solid components can be determined by the same method described for the coating solution (S).

[0119] There are no particular limitations on the method of applying coating liquid (T) in the same way as coating liquid (S), and known methods can be used.

[0120] The conditions for solvent removal (drying) after coating the coating liquid (T) in step (III) can be the same as the conditions for drying after coating the coating liquid (S) in step (I).

[0121] [Process (IV)] Before performing step (I), the layer (Z) may be formed after the substrate (X) has undergone surface treatment as required. Step (IV) may include: applying a coating liquid (R) containing a polyurethane-based resin or a polyester-based resin and a solvent, more preferably a coating liquid (R) containing a PVA-based resin, a polyester resin and a solvent, onto the substrate (X), and then removing the solvent to form the layer (Z).

[0122] As a means of obtaining a coating solution (R) comprising a PVA-based resin, a polyester-based resin, and a solvent, the PVA-based resin, polyester-based resin, and solvent can be directly mixed, or a solution or dispersion comprising a PVA-based resin can be mixed with a solution or dispersion comprising a polyester-based resin. From the viewpoint of solution uniformity, it is preferable to obtain the coating solution (R) by mixing an aqueous solution of a PVA-based resin with a dispersion of a polyester-based resin.

[0123] There are no particular limitations on the solvent used in the coating liquid (R), but water is preferred as the main component, and it can be water alone. Additionally, when water is the main component, alcohols such as methanol, ethanol, and isopropanol are preferred as other solvents.

[0124] From the viewpoint of the storage stability of the coating solution and its coatability to the substrate, the solid content concentration of the coating solution (R) is preferably 0.01 to 10% by mass. The aforementioned solid content concentration can be calculated, for example, by dividing the mass of the solid content remaining after distilling off the solvent of the coating solution (R) by the mass of the coating solution (R) supplied for processing.

[0125] There are no particular limitations on the coating of the coating liquid (R), and known methods can be used. Examples of coating methods include casting, dipping, roller coating, gravure coating, screen printing, reverse coating, spraying, kiss coating, die coating, metering rod coating, sealing knife coating, curtain coating, and bar coating.

[0126] There are no particular limitations on the solvent removal method for the coating liquid (R) after it has been applied to the substrate (X), and known drying methods can be used. Examples of drying methods include hot air drying, hot roller contact drying, infrared heating, and microwave heating.

[0127] [Electronic devices] The electronic device obtained using the multilayer structure of the present invention includes an electronic device body and a protective sheet protecting the surface of the electronic device body. The protective sheet for the electronic device of the present invention comprises the multilayer structure of the present invention. The protective sheet for the electronic device of the present invention may be composed solely of the multilayer structure of the present invention, or it may be composed of the multilayer structure of the present invention and other components. The protective sheet for the electronic device of the present invention has high water vapor barrier properties. Therefore, by using the protective sheet of the present invention, it is possible to obtain an electronic device with less degradation in harsh environments. For example, in the case of use in electronic paper substrate films, it can be suitable as a protective material for inks in electronic paper that are easily affected by moisture.

[0128] The electronic device of the present invention can be a photoelectric conversion device, an information display device, or a lighting device. Examples of photoelectric conversion devices include various solar cells and other photoelectric conversion devices. Examples of information display devices include liquid crystal displays, organic EL displays, plasma displays, electronic paper, and other information display devices. Examples of lighting devices include LED lighting, organic EL lighting, and other lighting devices.

[0129] The electronic device of the present invention is particularly preferably used as a device comprising optical elements. The optical elements are appropriately selected according to the intended use of the electronic device according to the present invention. Here, the optical element in the present invention refers to an element having an optical function, such as, for example, an information display function, a light-emitting function, etc. When using an element having an information display function as the aforementioned optical element, the electronic device of the present invention can be used as an information display device; when using an element having a light-emitting function as the optical element, the electronic device of the present invention can be used as a light-emitting device (illumination device).

[0130] Examples of optical elements with information display functions include liquid crystal cells used in liquid crystal display devices, organic EL elements used in organic EL display devices, and electronic paper elements (particle-moving type, liquid crystal type, electrochemical type, etc.) used in electronic paper devices. Here, as the aforementioned optical elements, by using liquid crystal cells, the optical device of the present invention forms a liquid crystal display device; by using organic EL elements, an organic EL display device is formed; and further, by using electronic paper elements, an electronic paper device is formed.

[0131] There are no particular limitations on the liquid crystal units, organic EL elements, and electronic paper components mentioned above; generally known components can be used.

[0132] The multilayer structure of the present invention can also be used as a substrate film, such as a substrate film for LCDs, organic ELs, and electronic paper. In this case, the multilayer structure can serve as both a substrate and a protective sheet. Furthermore, the electronic device to which the protective sheet is applied is not limited to the examples described above, and can include, for example, IC tags, optical communication devices, and fuel cells.

[0133] The protective film for electronic devices of the present invention may include a surface protective layer disposed on one surface of a multilayer structure. As the surface protective layer, a resin-formed layer with high transparency and resistance to damage is preferred. Furthermore, for devices such as solar cells that are sometimes used outdoors, the surface protective layer is preferably formed of a resin with high weather resistance (e.g., light resistance). Additionally, when protecting surfaces that require light transmission, a surface protective layer with high light transmittance is preferred. Examples of materials for the surface protective layer (surface protective film) include, for example, acrylic resins, polycarbonate, polyethylene terephthalate, polyethylene naphthalate, cellulose triacetate, ethylene-tetrafluoroethylene copolymer (ETFE), polytetrafluoroethylene, 4-fluoroethylene-perchloroalkoxy copolymer, 4-fluoroethylene-6-fluoropropylene copolymer, 2-ethylene-4-fluoroethylene copolymer, poly(3-fluorochloroethylene), polyvinylidene fluoride, and polyvinyl fluoride.

[0134] To improve the durability of the surface protective layer, various additives (such as UV absorbers) can be added. A preferred example of a surface protective layer with high weather resistance is an acrylic resin layer containing a UV absorber. Examples of UV absorbers include, but are not limited to, benzotriazole, benzophenone, salicylate, cyanoacrylate, nickel, and triazine UV absorbers. Additionally, other stabilizers, light stabilizers, antioxidants, etc., can be used in combination.

[0135] Furthermore, to improve the durability of the surface protective layer, a weather-resistant coating, such as a hard coating, can be applied to the surface. There are no particular limitations on the type of coating; known materials can be used.

[0136] There are no particular limitations on the composition of the protective film; sometimes, for example, the following composition is suitable.

[0137] (1) Multi-layer structure (2) Multilayer structure / adhesive layer / polyethylene terephthalate (3) Multilayer structure / adhesive layer / cellulose triacetate (4) Multilayer structure / adhesive layer / ETFE. Example

[0138] Next, embodiments will be provided to illustrate the present invention in more detail. However, the present invention is not limited to these embodiments at all, and various modifications can be made by those skilled in the art within the scope of the technical concept of the present invention. The analysis and evaluation in the following embodiments and comparative examples are carried out in the following manner.

[0139] <Materials used in the Examples and Comparative Examples> Substrate (X) • PET25: Biaxially stretched polyethylene terephthalate film; manufactured by Toray Industries, Inc., "LUMIRROR (registered trademark) S105" (trade name), thickness 25μm • PET50: Biaxially stretched polyethylene terephthalate film; manufactured by Toray Industries, Inc., "LUMIRROR (registered trademark) U403" (trade name), thickness 50μm Polyvalent metal salts (F) ·F-1:Zn(OAc)2·2H2O (manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., zinc acetate dihydrate, pKa of acetic acid 4.57, solubility in water 40g / 100mL) F-2:Mg(OAc)2·4H2O (manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., magnesium acetate tetrahydrate, pKa of acetic acid 4.57, solubility in water exceeding 40g / 100mL) ·F-3:Ca(OAc)2·H2O (manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., calcium acetate monohydrate, pKa of acetic acid 4.57, solubility in water exceeding 30g / 100mL) F-4: ZnC l2 (Manufactured by Fujifilm and Koko Pure Chemical Industries, Ltd., zinc chloride, pKa of hydrochloric acid -5.90, solubility in water exceeds 400g / 100mL) F-5: ZnO (manufactured by Fujifilm and Koh Genuine Chemicals Co., Ltd., zinc oxide, pKa of water 15.74, solubility in water less than 1g / 100mL) F-6: MgO (manufactured by Fujifilm and Koh Genuine Chemicals Co., Ltd., magnesium oxide, pKa of water 15.74, solubility in water ≥ 400g / 100mL) F-7: CaCO3 (manufactured by Fujifilm and Koh Genuine Chemicals Co., Ltd., calcium carbonate, pKa of carbonic acid 6.35, solubility in water less than 1g / 100mL) <Evaluation Methods> (1) Thickness The multilayer structures obtained in the examples and comparative examples were cut using a focused ion beam (FIB) to prepare cross-sectional sections for observation. The prepared sections were fixed to a sample stage with carbon tape and subjected to platinum ion sputtering for 30 seconds at an accelerating voltage of 30 kV. The cross-sections of the multilayer structures were observed using a field emission transmission electron microscope, and the thickness of each layer and the thickness of the multilayer structure were calculated. The measurement conditions are shown below.

[0140] Device: JEM-2100F manufactured by Nippon Electronics Co., Ltd. Accelerating voltage: 200kV Multiplier: 250,000x (2) Water vapor transmission rate (WVTR) For the multilayer structures obtained in the examples and comparative examples, samples were mounted on a water vapor transmission rate measuring apparatus with the substrate layer facing the carrier gas side, and the water vapor transmission rate was measured according to the isobaric method of ISO 15106-3:2003. The measurement conditions are shown below. It should be noted that when the multilayer structure is symmetrically configured, the sample was mounted with one side facing the carrier gas side for measurement.

[0141] Device: MOCONAQUATRAN2 manufactured by MODERNCONTROL Temperature: 40℃ Humidity on the water vapor supply side: 90%RH Carrier gas side humidity: 0%RH (3) The total area of ​​the interparticle void portion of layer (Y) For the multilayer structures obtained in the examples and comparative examples, the total area of ​​the interparticle voids in layer (Y) was calculated using ultra-high resolution field emission scanning electron microscopy. Specifically, 10 points at arbitrary locations on layer (Y) were observed using ultra-high resolution field emission scanning electron microscopy, and the total area of ​​the interparticle voids observed within a 600nm × 600nm range in the center of the field of view was calculated using image analysis software (ImagePro+). After planarization and noise reduction, the voids (dark areas) were segmented from other areas by binarization with an average brightness value below -2σ, and the area of ​​the voids was calculated. The measurement conditions are shown below. The average value of the calculated values ​​at the 10 points was obtained as the measured values.

[0142] Device: Hitachi High Technology Corporation SU8010 Accelerating voltage: 0.5kV Multiplier: 100,000x <Example of manufacturing coating liquid (S-1)> 230 parts by mass of distilled water were heated to 70°C with stirring. 88 parts by mass of aluminum triisopropoxy were added dropwise to this distilled water over 1 hour, and the temperature was gradually increased to 95°C, allowing hydrolysis and condensation to occur through distillation of the resulting isopropanol. 4.0 parts by mass of a 60% by mass aqueous solution of nitric acid were added to the resulting liquid, and the mixture was stirred at 95°C for 3 hours to degelatinate the aggregates of the hydrolyzed condensate particles. The liquid was then concentrated to a solids concentration of 10% by mass (calculated as alumina) to prepare a liquid containing metal oxide (A). 49.92 parts by mass of distilled water were added to 25.29 parts by mass of the resulting liquid containing metal oxide (A), and the mixture was stirred until homogeneous to obtain a dispersion. Next, while maintaining the liquid temperature at 5°C, 4.08 parts by mass of an 85% by mass aqueous solution of phosphoric acid and 18.80 parts by mass of a methanol solution were added dropwise while stirring the dispersion. Further, 1.90 parts by mass of a 23.9% zinc acetate aqueous solution was obtained by dissolving 28.6 parts by mass of zinc acetate dihydrate in 71.4 parts by mass of distilled water and added dropwise. After the addition was completed, the mixture was stirred for another 30 minutes to obtain the coating solution (S-1).

[0143] <Examples of manufacturing coating liquids (S-2) to (S-10), (CS-1) to (CS-7)> Except for changing the types and mass fractions of each main component according to Table 1, coating solutions (S-2) to (S-10) and (CS-1) to (CS-7) were prepared using the same method as coating solution (S-1). It should be noted that coating solution (CS-1) did not contain an aqueous solution of polyvalent metal salt (F), while coating solutions (CS-2) to (CS-5) contained it in solid form.

[0144] [Table 1] .

[0145] <Example of manufacturing coating liquid (R-1)> 4.8 parts by weight of PVA "KURARAYPOVAL (registered trademark) 48-80" were mixed with 95.2 parts by weight of water and stirred at room temperature for 5 hours to dissolve "KURARAYPOVAL (registered trademark) 48-80", thus obtaining an aqueous PVA solution. Next, 0.8 parts by weight of polyester-based aqueous dispersion "ELITEL (registered trademark) KA-5071S" (manufactured by Uniqlo Co., Ltd.), 1.2 parts by weight of the aforementioned aqueous PVA solution, 68.1 parts by weight of water, and 29.9 parts by weight of methanol were mixed and stirred for 30 minutes to obtain the coating solution (R-1).

[0146] <Example 1> Using PET50 as the base layer (X), a corona treatment device TEC-4AC manufactured by Kasuga Electric Co., Ltd. was used at 130 W·min / m 2 The strength of the substrate (X) was determined by surface treatment on one side. A coating solution (R-1) was applied to one side of the surface-treated substrate using a bar coater to achieve a dried thickness of 10 nm. The coated film was dried at 140 °C for 1 minute, forming a layer (Z) on one side of the substrate. A coating solution (S-1) was then applied to one side of the substrate where layer (Z) was formed, using a bar coater, to achieve an average dried thickness of 0.4 μm. The coated film was dried at 120 °C for 3 minutes, followed by heat treatment at 180 °C for 1 minute, forming a precursor layer for layer (Y) on layer (Z), resulting in a laminate (substrate (X) / layer (Z) / layer (Y) precursor layer). The resulting laminate was heat-treated at 210 °C for 1 minute to obtain a multilayer structure of substrate (X) (50 μm) / layer (Z) (10 nm) / layer (Y) (0.4 μm). For the obtained multilayer structure, the total area of ​​the WVTR and the interparticle void portion of the layer (Y) was determined based on the methods described in the above evaluation methods (2) and (3). The results are shown in Table 2.

[0147] <Examples 2-11, Comparative Examples 1-7> Except for changing the type of coating liquid (S) and the layer composition as described in Table 2, a multilayer structure was fabricated and evaluated using the same method as in Example 1. The results are shown in Table 2. It should be noted that in Example 11, a multilayer structure was fabricated using the same method as in Example 1, except that the coating liquid (S) was directly applied to the corona-treated surface of the substrate (X) instead of forming a layer (Z).

[0148] <Example 12> In Example 1, after fabricating a laminate (precursor layer of substrate (X) / layer (Z) / layer (Y)), corona treatment, layer (Z) formation, and layer (Y) precursor layer formation were performed on the side of substrate (X) where the unlaminated layer (Z) was not laminated, in the same manner as in Example 1, to fabricate a laminate having precursor layers of layer (Z) and layer (Y) on both sides of substrate (X) (precursor layer of layer (Y) / layer (Z) / substrate (X) / layer (Z) / layer (Y) precursor layer). The resulting laminate was heat-treated at 210°C for 1 minute to obtain a multilayer structure of layer (Y) (0.4 μm) / layer (Z) (10 nm) / substrate (X) (50 μm) / layer (Z) (10 nm) / layer (Y) (0.4 μm). For the obtained multilayer structure, the total area of ​​the interparticle void portion of WVTR and layer (Y) was measured based on the methods described in the above evaluation methods (2) and (3). The results are shown in Table 2.

[0149] <Example 13> Except for changing the type of substrate (X) as described in Table 2, a multilayer structure was fabricated and evaluated using the same method as in Example 12. The results are shown in Table 2.

[0150] [Table 2] .

[0151] For the multilayer structures obtained in Examples 1-4, TOF-SIMS was measured under the following conditions, and the acetate ion detection amount of zinc acetate used as a multivalent metal salt (F) in Examples 1-4 was compared. Specifically, the ratio of the fragment ion intensity (S_acetate ion) identified by TOF-SIMS at the outermost surface of layer (Y) to the total detected ion intensity (S_acetate ion / S_total) was calculated.

[0152] <TOF-SIMS Conditions> The multi-layer structure obtained in the example was cut into 10mm×10mm pieces and placed on the measuring platform via aluminum blocks. The samples were then measured.

[0153] Measurement device: TOF.SIMS5 (manufactured by ION-TOF) Analysis software: Surface Lab 6 (manufactured by ION-TOF) Primary ion source: Bi3++ Measurement current: 0.2 pA at 25 keV (10 kHz) Measurement range: 200μm × 200μm Pixel count measured: 128Pix × 128Pix Charge neutralization condition: using FloodGun Regarding the ratio of measured results (S_acetate ions / Stotal), it was 0.0008 in Example 1, 0.0010 in Example 2, 0.0018 in Example 3, and 0.0021 in Example 4. These results indicate a correlation between the zinc acetate content and the amount of acetic acid detected by TOF-SIMS.

Claims

1. A multilayer structure comprising a substrate (X) and a layer (Y) stacked on the substrate (X). Layer (Y) contains the reaction product (D) of a metal oxide (A) containing aluminum atoms and an inorganic phosphorus compound (BI), as well as a polyvalent metal salt (F). In layer (Y), the number (N) of moles (M) of metal atoms (M) constituting the metal oxide (A) M The number of moles of inorganic phosphorus compounds (BI) and N P The ratio of (N) M / N P The condition satisfies a value of 1.0 or higher and 2.4 or lower, and the molar number (N) of the metal ions (G) constituting the polyvalent metal salt (F) is... G The number of moles (N) of the metal atoms (M) constituting the metal oxide (A) and the number of moles (N) of the metal atoms (M) constituting the metal oxide (A). M The ratio of (N) G / N M () is above 0.03 and below 0.25, The solubility of polyvalent metal salts (F) in water at 25°C is over 20 g / 100 mL. The acid dissociation constant (pKa) of the conjugate acid (H') of the anion (H) constituting the polyvalent metal salt (F) is greater than 1.

83.

2. The multi-layer structure according to claim 1, wherein, The metal ion (G) that constitutes the polyvalent metal salt (F) is the zinc ion.

3. The multi-layer structure according to claim 1 or 2, wherein, The anion (H) that constitutes the polyvalent metal salt (F) has a carboxylate anion structure.

4. The multi-layer structure according to claim 1 or 2, wherein, The total area of ​​the interparticle voids in layer (Y) within the range of 600 nm × 600 nm is 1500–2000 nm. 2 Within the range.

5. The multilayer structure according to claim 1 or 2, wherein, It has a structure in which a substrate (X) and a layer (Y) are stacked together through a layer (Z).

6. A method for manufacturing a multilayer structure according to claim 1 or 2, comprising: A coating solution (S) comprising a metal oxide (A), an inorganic phosphorus compound (BI), a polyvalent metal salt (F), and a solvent is applied to a substrate (X), followed by solvent removal to form a precursor layer (Y); and... Process (II) is to heat-treat the precursor layer of layer (Y) to form layer (Y).

7. A protective sheet for electronic devices, comprising the multilayer structure as described in claim 1 or 2.

8. The protective sheet according to claim 7 is a protective sheet for protecting the surface of a photoelectric conversion device, an information display device, or a lighting device.

9. An electronic device having the protective sheet as described in claim 8.

Citation Information

Patent Citations

  • Control device for vehicle

    JP2024055378A

  • Composite structure, packaging material and molded article each produced using same, process for production of composite structure, and coating solution

    WO2011122036A1

  • Multilayer structure and method for producing same, packaging material and product which use same, electronic-device protective sheet, and coating liquid

    WO2015141225A1